AD dementia risk in late MCI, in early MCI, and in subjective memory impairment. Issue 1 (1st February 2013) - Jessen, Frank; Wolfsgruber, Steffen; Wiese, Birgitt; Bickel, Horst; Mösch, Edelgard; Kaduszkiewicz, Hanna; Pentzek, Michael; Riedel‐Heller, Steffi G.; Luck, Tobias; Fuchs, Angela; Weyerer, Siegfried; Werle, Jochen; et al.
Abstract: Objective: To compare the risk of developing Alzheimer's disease (AD) dementia in late mild cognitive impairment (LMCI), early MCI (EMCI), and subjective memory impairment (SMI) with normal test performance. Methods: The baseline sample (n = 2892) of the prospective cohort study in nondemented individuals (German Study on Aging, Cognition and Dementia in Primary Care Patients) was divided into LMCI, EMCI, SMI, and control subjects by delayed recall performance. These groups were subdivided by the presence of self‐reported concerns associated with experienced memory impairment. AD dementia risk was assessed over 6 years. Results: Across all groups, risk of AD dementia was greatest in LMCI. In those with self‐reported concerns regarding their memory impairment, SMI and EMCI were associated with a similarly increased risk of AD dementia. In those subgroups without concerns, SMI was not associated with increased risk of AD dementia, but EMCI remained an at‐risk condition. Conclusions: SMI and EMCI with self‐reported concerns were associated with the same risk of AD dementia, suggesting that pre‐LMCI risk conditions should be extended to SMI with concerns.